STEM Approach to 4C Skills in Elementary School Students: A Systematic Literature Review - Sari, Lidya Savana; Kaepah, Kaepah; Fitriani, Pipit; Tresnawati, Nailah; Khodari, Rahmad (Scientiae Educatia: Jurnal Pendidikan Sains, 2024)
The STEM approach is increasingly significant in elementary school learning because it can develop 4C skills such as critical thinking, creativity, collaboration, and communication. This study aims to identify the STEM approach to developing 4C skills in elementary school students through a Systematic Literature Review (SLR) using the PRISMA method with a time period of 2014-2024. This study reviews articles and journals published in the last ten years, focusing on methods and results relevant to the STEM approach in elementary schools. The analysis shows that the STEM approach to improving 4C skills in elementary schools can be grouped into three product categories: simple technology, simple technology from used goods, and prototypes. The most common category is simple technology, which promotes critical thinking, creativity, communication, and collaboration, all of which are important in the STEM approach. The findings show that simple technologies such as raft boats, animal recycling concept dioramas, and electrical conduction from plastic bottles significantly increase student engagement and motivation. The study concluded that the STEM approach can improve students' 4C skills (critical thinking, creativity, communication, and collaboration), and it is important to use products that can encourage students to integrate 4C skills with STEM, resulting in creative and innovative products. Schools and teachers must implement these technology-based tools and methods to maximize students' learning potential.